CROWRDFUNDING DONASI: STUDI ITERATIVE DEVELOPMENT DALAM MENGIMPLEMENTASIKAN FEEDBACK PADA PENGEMBANGAN WEBSITE - Steven; Heru Wijayanto Ariandono (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
TheUtopia is a startup social enterprise or social business company that combines the basic concept of trading, which is seeking profit with our obligation to help the social environment, TheUtopia provides a fundraising platform to help donors to make donations easily and safely and also with TheUtopia platform, helping orphanages (campaign) to reach out with the wider community in order to achieve the goals you want to achieve. The purpose of this research is to find out how to develop and implement a social crowdfunding strategy in the batam community using iterative development. The method used in this research is iterative method and the data collection technique used is interview. The website is designed using XAMPP programming with the Laravel Framework. The existence of TheUtopia website can help donors make donations to orphanages in Batam, whether they are known to the public or not. The result of this research is that a social crowdfunding website called TheUtopia can run according to its function and can be accessed by the public.